The Coexistence of Counsellor Role Variability and Counselling Consensus: A Research Challenge - Klas, Leroy D. (Canadian Journal of Counselling and Psychotherapy, 2012)
The Jevne (1981) study described the role discrepancies that still exist in counselling in Canada and outlined the competencies deemed most crucial for the counselling practitioner. This article points out that there appears to be more confusion over counsellor roles than over the competencies counsellors need to carry out those roles. The writer then poses five research questions whose further exploration may shed some light on how roles and competencies evolve and how they may be better integrated.